You have a brain - Carson, Ben; Lewis, Gregg, 1951-; Lewis, Deborah Shaw, 1951- (Zondervan, 2015)
Throughout his life, renowned neurosurgeon Dr. Benjamin Carson has needed to overcome many obstacles: his father leaving the family, being considered stupid by his classmates in grade school, growing up in inner-city Detroit, and having a violent temper. But Dr. Carson didn't let his circumstances control him and instead discovered eight principles that helped shape his future... Dr. Carson unpacks the eight important parts of Thinking Big: Talent, Honesty, Insight, being Nice, Knowledge, Books, In-Depth learning, and God, and presents the stories of people who demonstrated those things in his life. By applying the idea of THINK BIG to your life, and by looking at those around you as well, you too can overcome obstacles and work toward achieving your dreams.